Seminar Pengabdian Masyarakat Internasional dalam Pengaplikasian AI di Kehidupan Sehari-Hari Bagi Siswa-Siswi SMA Muhammadiyah Program Khusus Kotabarat Surakarta - Muhamad Aditya Yulianto; Luki Sri Anggorowati; Arif Nugroho Rachman; Unna Ria Safitri (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
The International Community Service Seminar on the Application of Artificial Intelligence (AI) for students of SMA Muhammadiyah Program Khusus Kotabarat Surakarta was conducted to enhance digital literacy and provide practical understanding of AI utilization in daily life and learning activities. The program aimed to introduce basic concepts of artificial intelligence, its functions, benefits, and challenges in modern education. Through presentations, interactive discussions, and quizzes, participants were exposed to real-life applications of AI such as digital assistants, personalized learning systems, and time management tools. The seminar involved participants from Indonesia and Malaysia, creating a cross-cultural learning environment that enriched the discussion. Both students and teachers gained improved understanding of how AI can support adaptive and effective learning processes. The activity highlighted the importance of responsible technology use in education. Integrating AI into learning environments was found to improve creativity, efficiency, and engagement among participants while also supporting teachers in administrative and instructional tasks.